2007
DOI: 10.1021/la063236a
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Rheology of an Ultrathin Nanocrystalline Film Formed at the Liquid/Liquid Interface

Abstract: We report the interfacial properties of monolayers of Ag nanoparticles 10-50 nm in diameter formed at the toluene-water interface under steady as well as oscillatory shear. Strain amplitude sweep measurements carried out on the film reveal a shear thickening peak in the loss moduli (G") at large amplitudes followed by a power law decay of the storage (G') and loss moduli with exponents in the ratio 2:1. In the frequency sweep measurements at low frequencies, the storage modulus remains nearly independent of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 20 publications
6
38
0
Order By: Relevance
“…Both present a maximum at intermediate SiOH content. For particles of 34% SiOH, the yield strain γ Y is quite high at 5%, much higher than that of < 1% for silver nanoparticles adsorbed at an oil-water interface [30]. However, it is close to that of monolayers of insoluble surfactants and proteins [31,32].…”
Section: Shear Propertiesmentioning
confidence: 99%
“…Both present a maximum at intermediate SiOH content. For particles of 34% SiOH, the yield strain γ Y is quite high at 5%, much higher than that of < 1% for silver nanoparticles adsorbed at an oil-water interface [30]. However, it is close to that of monolayers of insoluble surfactants and proteins [31,32].…”
Section: Shear Propertiesmentioning
confidence: 99%
“…The interface between Wa nd an aromatic hydrocarbon such as toluene is utilized in solvente xtraction, [23,24] and over the past several decades the formation of nanoparticles and thin-layer films at the W j toluene interface has been studied extensive-ly. [25][26][27][28][29][30] To the best of our knowledge,h owever,t here are no direct experimental data on VITIES at the W j toluene interface.Use of am icro-electrode and tetrahexylammonium perchlorate (THexA + ClO 4 À )a st he SE enablet he observation of the reversible response for the redox reaction of ferrocene [31] or porphyrins [32,33] in toluene, because the micro-electrode reduces the effect of the ohmic drop. The effect of the addition of the RTIL [trihexyl(tetradecyl)phosphonium tris(pentafluoroethyl)trifluorophosphate, aph4.cph12]t ot oluene has been demonstratedi nahomogeneous electrochemical system using macro-disc electrodes, and it was observed that 0.4 m (m = mol dm À3 )a ph4.cph12 in toluene induces conductivity in the toluene solutiona ta mbient temperature.…”
mentioning
confidence: 99%
“…The interface between Wa nd an aromatic hydrocarbon such as toluene is utilized in solvente xtraction, [23,24] and over the past several decades the formation of nanoparticles and thin-layer films at the W j toluene interface has been studied extensive-ly. [25][26][27][28][29][30] To the best of our knowledge,h owever,t here are no direct experimental data on VITIES at the W j toluene interface.…”
mentioning
confidence: 99%
“…54 Both Efrima and Rao have reported the synthesis and properties of silver lms that have been at the interface between two immiscible liquids using other precursors. 55,56 The charge transport characteristics of these lms are unknown.…”
Section: Resultsmentioning
confidence: 99%